AISI D2 Tool Steel: Modelling and Optimizing Process Parameters for Wire Electrical Discharge Machining - Aneesh Kumar (International Journal of Advanced Science and Technology, 2020)
For preparing dies and punches a significant material should have exceptional thermo-mechanical properties together with superior wear resistance. The AISI D2 tool steel are the material that are finding widespread applications in a lot of manufacturing industries. For making such complex shapes and intricate designs as used in dies and punches, a highly developed method must be employed while machining those heat treated tool steels. Wire Electro Discharge Machining (WEDM) is one of the highly developed and sophisticated methods. During machining through WEDM with optimization of performance characteristics namely Material Removal Rate and Surface Roughness appropriate choices of process parameters are required.